Pedagogical and psychological features of the development of students' creative activity by teachers - Mavlonov Ulugbek Tursunaliyevich (Genius Journals, 2022)
The covered topic in the article shows the importance of educators to the worldview, knowledge and education, creative activity and formation of professional skills of students, who are necessary personnel for our future society. The objectives of the study were highlighted the experience and effectiveness of the activities that professors and teachers should follow in the course of their work. The methods of working with creative students, the intended goals and objectives, pedagogical and psychological characteristics and ways of their implementation are indicated. The opportunities of teachers to develop creative student management skills are based.
Keywords: Creative students; development of talent; creativity; exhibitions